The role of career exploration in career decision participants - Hermawan, Rio; Farozin, Muh (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2018)
AbstractIn the digital era, humans were required to be more able to develop themselves according to potentials owned so that it was important for each individual to understand his/her ability and also able to develop other various skills. Career selection was one of most important decision making processes in individual living. However, today learners were facing various different career environment both in characteristics as well as their kinds, and also trend of learners who were less understand potentials owned both due to their ignorance as well as due to they do not explore nor develop potentials owned so that it gives a negative impact for himself/herself in a career decision so that needed roles of career exploration in a career decision making. Therefore, understanding, awareness and acceptance towards potentialsowned by each individual is necessary in supporting learner career in the future. Efforts conducted in preparing learner career were very much. One of efforts in preparing it was by exploring career. Career exploration was defined as an individual desire to explore or search information towards career information sources. Roles of career exploration in a career decision was related to a career exploration region includes selection orientation, self-exploration, environmental exploration, in-depth environmental exploration, decision status and commitment.